Testing the effect of host availability on endobiont diversity: proposing the single hotel hypothesis - Tal Idan; Sigal Shefer; Giorgos Chatzigeorgiou; Vasilis Gerovasileiou; Liron Goren (Scientific Reports)
Abstract This study investigates the determinants of endobionts diversity within habitat-forming organisms, employing concepts from Island Biogeographic Theory (IBT) as a prospective explanatory framework. Sponges have long been considered “living hotels” due to the great diversity and abundance of their associated fauna. Various factors have been proposed to influence the composition and diversity of sponge-associated fauna, often relating to individual sponge characteristics, such as volume and oscular diameter. However, studies frequently contradict when identifying the main determinant. Focusing on two common massive sponge species, Agelas oroides and Sarcotragus foetidus, we collected, dissected, and analyzed 18 sponge specimens of A. oroides and 12 of S. foetidus from three sites in Crete, Greece (Eastern Mediterranean Sea). The sponges hosted 943 macroinvertebrates belonging to 94 different taxa, half of which were polychaetes. Crustaceans were the most abundant group, with over 50% of the individuals. Contrary to IBT predictions, A. oroides from areas with lower sponge abundance (i.e., “single hotel in town”), exhibited higher endofauna densities and richness. Notably, S. foetidus, which hosted large numbers of snapping shrimps, presented a different pattern, highlighting the importance of species-specific interactions on endobiont communities. Additionally, the reproductive state of S. foetidus correlated with increased endobiont richness, suggesting a potentially overlooked aspect of sponge-endobiont interactions related to the sponge’s reproductive state. These results emphasize the importance of sponges as “living hotels” and sponge communities as sources of biodiversity and highlight the complex influence of habitat availability and species-specific interactions on sponge-associated fauna.